(untitled) (Emerging Indexing of Global Multidisciplinary Journal, 2025)
Underutilized edible micrograins represent an emerging category of nutritionally dense biological resources with significant potential for product enhancement in functional food systems. Despite their rich micronutrient composition and bioactive potential, these micrograins remain largely underexploited in industrial food formulation and dietary intervention programs. This paper systematically examines their health attributes and evaluates their integration potential within modern product development frameworks. The study adopts a structured analytical approach combining nutritional science perspectives with system-based modeling of data-driven food enhancement strategies. Interestingly, the conceptual framing extends beyond conventional food science by integrating principles derived from secure data management systems in healthcare and cloud computing environments. This interdisciplinary approach is informed by frameworks of secure information sharing and controlled access systems (Benaloh et al., 2009; Li et al., 2010), enabling a novel interpretation of how nutritional data and food composition databases can be managed in scalable systems. The findings suggest that micrograins exhibit strong functional properties, including high micronutrient density, antioxidant potential, and metabolic regulatory effects. However, their industrial utilization is limited by inconsistent classification systems, lack of standardized nutritional databases, and insufficient integration into large-scale food engineering models. The study further highlights that secure and structured data-sharing frameworks, similar to attribute-based encryption systems used in electronic health records (Wang et al., 2011; Wan et al., 2012), can significantly improve traceability and optimization of micrograin-based product development. Additionally, the research incorporates insights from digital health security models to propose a conceptual framework for nutritional data protection and personalized dietary modeling (Löhr et al., 2010; Mandl et al., 2001). This is particularly relevant in precision nutrition systems where individual dietary responses to micrograin-based products may be optimized. The study concludes that underutilized edible micrograins hold substantial promise for functional food innovation, but their adoption requires integrated systems combining nutritional science, food engineering, and secure data-driven modeling frameworks. The work contributes to bridging the gap between agricultural biodiversity and technologically advanced food systems.